Global burden of acute lower respiratory infections due to respiratory syncytial virus in young children: a systematic review and meta-analysis - Nair, Harish; Nokes, D James; Gessner, Bradford D; Dherani, Mukesh; Madhi, Shabir A; Singleton, Rosalyn J; O'Brien, Katherine L; Roca, Anna; Wright, Peter F; Bruce, Nigel; Chandran, Aruna; Theodoratou, Evropi; et al. (The Lancet (British edition), 2010)
The global burden of disease attributable to respiratory syncytial virus (RSV) remains unknown. We aimed to estimate the global incidence of and mortality from episodes of acute lower respiratory infection (ALRI) due to RSV in children younger than 5 years in 2005. We estimated the incidence of RSV-associated ALRI in children younger than 5 years, stratified by age, using data from a systematic review of studies published between January, 1995, and June, 2009, and ten unpublished population-based studies. We estimated possible boundaries for RSV-associated ALRI mortality by combining case fatality ratios with incidence estimates from hospital-based reports from published and unpublished studies and identifying studies with population-based data for RSV seasonality and monthly ALRI mortality. In 2005, an estimated 33·8 (95% CI 19·3–46·2) million new episodes of RSV-associated ALRI occurred worldwide in children younger than 5 years (22% of ALRI episodes), with at least 3·4 (2·8–4·3) million episodes representing severe RSV-associated ALRI necessitating hospital admission. We estimated that 66 000–199 000 children younger than 5 years died from RSV-associated ALRI in 2005, with 99% of these deaths occurring in developing countries. Incidence and mortality can vary substantially from year to year in any one setting. Globally, RSV is the most common cause of childhood ALRI and a major cause of admission to hospital as a result of severe ALRI. Mortality data suggest that RSV is an important cause of death in childhood from ALRI, after pneumococcal pneumonia and Haemophilus influenzae type b. The development of novel prevention and treatment strategies should be accelerated as a priority. WHO; Bill & Melinda Gates Foundation.